RETRACTED: Demokratisasi Konvensi HAM Relasi Islam dan Negara: Kondisi Indonesia - Abdul Jalil Salam (Jurnal Justisia : Jurnal Ilmu Hukum, Perundang-undangan dan Pranata Sosial, 2016)
This manuscript HAS BEEN RETRACTED on the request of the author. Therefore, a reasonable effort should be made to remove all references that links to this article.